Code Switching and Its Implications for Teaching in the English Language in Math Lessons by Early Childhood Education Teachers - Prabowo KA, AB; Ambarini, Ririn (KnE Social Sciences, 2022)
Interactions between students and between students and teachers are the key to successful learning. This study examines whether code-switching to using English for teaching Math in Semarang’s Early Childhood Education or PAUD programs can improve student interactions. This study investigated how early childhood education teachers implemented code-switching to English instructions for young learners. According to the findings of the study, early childhood educators utilized English, Indonesian, and Javanese interchangeably. The results indicated that the implications of code-switching in school are an approach to acquiring literacy because students can use different languages in a natural and meaningful manner while participating in classroom activities. The study shows that using code-switching in multilingual mathematics classrooms is a beneficial strategy to improve student interactions in classroom activities and is an effective method of transferring knowledge to students. The study further proves that code-switching implications do not result in a learning deficiency. Keywords: Code-switching, English for Young Learners, English for Math, Instruction